Petrogenesis of the Paleoproterozoic Näränkävaara layered intrusion, northern Finland, Part II : U-Pb ID-TIMS age and Sm-Nd isotope systematics - Järvinen, Ville; Halkoaho, Tapio; Konnunaho, Jukka; Heinonen, Jussi S.; Kamo, Sandra; Davey, Sarah; Bleeker, Wouter; Karinen, Tuomo; Rämö, O. Tapani (Bulletin of the Geological Society of Finland, 2022)
Several mafic-ultramafic layered intrusions were emplaced in the NE Fennoscandian Shield during a magmatic episode at 2.44 Ga. The Paleoproterozoic Näränkävaara layered intrusion, northern Finland, is one of the largest ultramafic bodies in the Fennoscandian Shield, with a surface area of 25 km x 5 km and a magmatic stratigraphic thickness of ~3 km. The intrusion comprises a 1.3 km-thick peridotitic–dioritic layered series (2436 ± 5 Ma) with two peridotitic reversals, and a 1.5–2 km thick basal dunite series mainly composed of olivine adcumulates (dated here). The intrusion has been studied since the 1960’s, but several questions regarding its structure and petrogenesis remain. The basal dunite shows several lithological features typical of komatiitic rather than intrusive olivine cumulates; namely, >1 km-thick “extreme” olivine adcumulates, some showing textures with bimodal grain sizes, oscillating variations in Mg# with stratigraphic height, and poikilitic chromite. With Archean greenstone belts nearby, it was previously hypothesized that the basal dunite series could represent an Archean komatiitic wall rock to the Paleoproterozoic layered series. However, our new U-Pb ID-TIMS baddeleyite age of 2441.7 ± 0.9 Ma for the basal dunite series shows that the basal dunite and layered series of the Näränkävaara intrusion are co-genetic. New whole-rock Sm-Nd isotope data from key stratigraphic units (initial εNd at 2440 Ma of -3.5 to -1.7) indicate that the intrusion was constructed from repeated emplacement of LREE-enriched high-MgO basaltic magmas that were mantle-derived and contaminated by crust, similarly to other Fennoscandian 2.44 Ga intrusions. The parental magmas show similar compositions regardless of stratigraphic position, suggesting that most wall rock contamination and homogenization had occurred before emplacement, with in situ contamination being a relatively minor process. The open-system features of the basal dunite suggest that it may have formed (at least partly) as a feeder channel cumulate, ...